Council for the Education and Training of Health Visitors: a case study of a statutory qualifying association in nursing - Wilkie, Elaine (The University of Edinburgh, 1980)
This study attempts to identify the interplay between the statutory qualifying associations in nursing, the service within which they operate and the climate of opinion in the profession they serve. Using a case study approach one such organisation is chosen as the vehicle far the exploration of the factors influencing the powers and responsibilities of a qualifying association and the significance of its relationship with the central government departments.